Analytical calculation of copper losses in litz-wire windings of gapped inductors - Stadler, Alexander; Huber, Raoul; Stolzke, Tobias; Gulden, Christof (IEEE Transactions on Magnetics, 2014)
Keywords: Air gaps; analytical models; eddy currents; electromagnetic analysis; inductors

A new generation of modular power inductors with minimum thermal resistance - Stadler, Alexander; Stolzke, Tobias; Gulden, Christof (2014 16th European Conference on Power Electronics and Applications, EPE-ECCE Europe 2014, 2014)
Keywords: Device simulation; Packaging; Passive component; Thermal design

Calculating phase currents for high frequency three phase inductors via the inductance matrix - Stolzke, Tobias; Stadler, Alexander; Gulden, Christof (2015 International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2015, 2015)

Comprehensive accuracy examination of electrical power loss measurements of inductive components for frequencies up to 1 MHz - Stolzke, Tobias; Ehrlich, Stefan; Joffe, Christopher; März, Martin (Journal of Magnetism and Magnetic Materials, 2019)
Keywords: Phase measurement; Soft magnetic; Inductive components; Core losses; Hysteresis losses

Design and simulation of thermally optimized filter inductors for a 1mw windmill demonstrator - Stadler, Alexander; Stolzke, Tobias; Gulden, Christof (2015 International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2015, 2015)

High frequency high current filter inductors with minimum thermal resistance - Stadler, Alexander; Stolzke, Tobias; Gulden, Christof (16th International Power Electronics and Motion Control Conference and Exposition, PEMC 2014, 2014)
Keywords: Inductors; Integrated design; Passive components; Thermal simulation

Investigation of magnetic properties from a manganese–zinc–ferrite polymer bonded material - Stolzke, Tobias; Dirnecker, Tobias; Schwarz, Julian; Frey, Lothar (International Journal of Applied Electromagnetics and Mechanics, 2018)
This paper presents a new type of a polymer bonded soft magnetic material (PBSMM) which can be used to create complex magnetic core geometries. The PBSMM consists of two separate materials, manganese zinc ferrite powder and polydimethylsiloxane (PDMS) as matrix material. The magnetic core losses of the PBSMM where analyzed at 10 kHz and 1 MHz with self-fabricated toroidal core samples by using a custom-made measurement setup in accordance with the IEC-62044-3 norm. The complex permeability was determined by evaluating impedance analyzer measurements between 10 kHz and 1 MHz. It is pointed out that the investigated material can be used for power electronic filter applications and opens the opportunity to create geometrical complex inductive component
Keywords: Soft magnetic-polymer; manganese–zinc–ferrite; high frequency

Investigation of magnetic properties from a manganese-zinc-ferrite polymer bonded material - Stolzke, Tobias; Dirnecker, Tobias; Schwarz, Julian; Frey, Lothar (International Journal of Applied Electromagnetics and Mechanics, 2019)
Keywords: high frequency; Soft magnetic-polymer; manganese-zinc-ferrite

Nonlinear inductors for active power factor correction circuits - Stadler, A.; Gulden, C.; Stolzke, Tobias (15th International Power Electronics and Motion Control Conference and Exposition, EPE-PEMC 2012 ECCE Europe, 2012)
Keywords: Passive component; Power factor correction; Simulation

Nonlinear power inductors for large current crest factors - Stadler, Alexander; Stolzke, Tobias; Gulden, Christof (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2012, 2012)

Optimized filter inductors for a 1MW windmill demonstrator with an objective to reduced converter size - Stadler, Alexander; Stolzke, Tobias; Gulden, Christof (17th European Conference on Power Electronics and Applications, EPE-ECCE Europe 2015, 2015)
Keywords: Device simulation; Packaging; Passive component; Thermal design; Wind energy

Simplifying Random Particle Structures within Soft Magnetic Composite Materials for the Optimization of 3D-FEM Simulations - Stolzke, Tobias; Schwarz, Julian; März, Martin (IEEE Transactions on Magnetics, 2024)
This paper investigates the simulative approximation for simplifying the complex random particle arrangement within a soft magnetic composite (SMC) material by cubic atomic lattice structures. The implemented 3D finite element model (FEM) can calculate the relative permeability of different particle arrangements in the form of a geometric replication of a volume section of the SMC material. We demonstrate the determination of the relative permeability in dependency of the volume fraction from an SMC material with the simulation and the results are consistent with established analytical formulas, based on the demagnetization factor and relative permeability of the soft magnetic particles. The utilization of cubic atomic lattice structures is investigated in respect of reducing the computational complexity. The four atomic lattice structures introduced here each correspond to a fixed volume fraction. By varying the relative permeability of the soft magnetic particles, the simulation results reveal a maximum achievable relative permeability for the polydisperse cubic face-centered particle structure of 45.5. Furthermore, the relative permeability of several self-manufactured toroidal SMC cores with different particle size distributions was measured, and we detailedly investigated the measurement uncertainty. The measurement results indicate that the particle size distribution has no influence on the relative permeability of the compound material. Especially the simulation model of the monodisperse cubic primitive particle structure with a volume fraction of 52.36 % replicates the measurement results with high conformity. In conclusion, it is possible to simplify the random particle structure in SMC materials within a specific range of volume fractions. Thereby, for volume fractions over 50 %, a tradeoff between model complexity and accuracy is necessary.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Analytical models; Lattices; Magnetostatic 3D-FEM Simulation; Magnetostatics; Permeability; Random Particle Structures; Relative Permeability; Soft Magnetic Composite; Soft magnetic materials; Solid modeling; Toroidal magnetic fields

The simulation of copper losses in litz-wire windings considering air gap fringing fields - Stadler, Alexander; Huber, Raoul; Stolzke, Tobias; Gulden, Christof (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, PCIM Europe 2013, 2013)